Das Gesetz gegen Doping im Sport in der Praxis - Eine Evaluierung The act against doping in sport in practice - An evaluation - Hoven, Elisa (Schriftenreihe zum deutschen, europäischen und internationalen Wirtschaftsstrafrecht, 2021)
The act against doping in sport stands at the end of an intensive legal discussion. The main points of contention were the introduction of a punishable ban on self-doping and the relationship between national criminal law and the law governing sports associations. Five years after the act came into force, the authors undertook an evaluation of its provisions and its practical application on behalf of the German Federal Government. The book uses case studies and interviews to illustrate the strengths and weaknesses of the act against doping in sport. In this way, the book serves both to understand national legal practice and to provide guidance for legislators and sports associations.